Does Primary Care Availability Mediate the Relationship Between Rurality and Lower Life Expectancy in the United States?. (October 2022) - Sharma, Arjun; Basu, Sanjay
Introduction: Rural counties in the United States have lower life expectancy than their urban counterparts and comprise the majority of primary care provider (PCP) shortage areas. We evaluated whether PCP availability mediates the relationship between rurality and lower life expectancy. Methods: We performed a mediation analysis on a panel dataset which included county-level estimates (N = 3103) for the years 2010, 2015, and 2017, and on a subset containing only rural counties (N = 1973), with life expectancy as the outcome variable, urbanity as the independent variable, and PCP density as the mediating variable. County-level socio-demographic data were included as covariates. Results and Conclusions: PCP density mediated 10.1% of the relationship between urbanity and life expectancy in rural counties. Increasing PCP density in rural counties with PCP shortages to the threshold of being a non-shortage county (>1 physician/3500 population, as defined by the Health Resources and Services Administration) would be expected to increase mean life expectancy in the county by 26.1 days (95% confidence interval [CI]: 11.4, 49.3) and increasing it to the standards recommended by a Secretarial Negotiated Rulemaking Committee would be expected to increase mean life expectancy by 65.3 days (95% CI: 42.6, 87.5). PCP density is a meaningful mediator of the relationship between urbanity and life expectancy. The mediation effect observed was higher in rural counties compared to all counties. Understanding how PCP density may be increased in rural areas may be of benefit to rural life expectancy.